Pengaruh Profesionalitas Dosen terhadap Capaian Pembelajaran Mahasiswa pada Program Studi Komunikasi dan Penyiaran Islam Fakultas Ushuluddin, Adab dan Dakwah IAIN Samarinda - Beta, A. Rivai (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2018)
This study aimed to look at the lecturers on competency of the the learning outcomes of students in the Communication and Islamic Broadcasting Study Programe Faculty of Ushuluddin, Adab and Dakwah IAIN Samarinda This research used quantitative methods by analyzing using regression analysis with SPSS 17 assistance. Communication and Islamic Broadcasting Faculty of Ushuluddin, Adab and Dakwah IAIN Samarinda, where the population of this research was 95 students of Communication and Islamic Broadcasting IAIN Samarinda and a sample of 77 people was taken by using the Simple Random Sampling method with Slovin formula. As a result, together the influence of lecturer competence on learning outcomes was 0.6% with a significance of 0.038 less than 0.05, which means that the effect is significant. Separately from the four lecturers' competencies namely 0.7% pedagogic competence, 0.6% professional, and 0.6% personality, towards learning achievement, where all three competencies had less than 0.05 so the effect is significant. The social competence of the lecturers only gives a small contribution of 0.2% which did not affect the learning outcomes of students of the Communication and Islamic Broadcasting Study Program of the Faculty of Ushuluddin, Adab and Da'wah of IAIN Samarinda, and the significance value is 0.203 greater than 0.05. significant. So that the need for improvement of social competence for lecturers.